290 DEPLETING REGULATORY T CELLS IS ASSOCIATED WITH IMPROVED IMMUNITY AND TUMOR CLEARANCE IN HUMAN CANCER. (1st January 2005) - Barnett, B.; Kryczek, I.; Cheng, P.; Zou, W.; Curiel, T. J.
Abstract : Despite a compelling logic, tumor immunotherapy has generally failed. Work by us and others suggests that this failure owes in part to tumor-mediated immune dysfunction. CD4+CD25+ regulatory T cells (Tregs) are thought to contribute to this dysfunction. In support, we show that in ovarian cancer patients, Tregs block tumor-specific immunity, promote tumor growth and predict poor survival. We hypothesize that depleting Tregs will improve immunity and improve therapeutic outcomes in cancer patients. Ontak is a recombinant protein fusing the CD25-binding domain of IL-2 to the active domain of diphtheria toxin. It was designed to kill CD4+CD25+ leukemia cells. We tested the hypothesis that Ontak kills CD4+CD25+ Tregs and thus improves immunity in cancer patients. Patients 1-3 (advanced-stage cancer of the ovary, breast or lung) received a single intravenous infusion of 9 μg/kg Ontak. Patient 4 had relapsed stage IIIC ovarian cancer and received a single dose of Ontak at 12 μg/kg. Blood immune cells from before and after treatment were enumerated and cytokines were studied by flow cytometry. T cell suppression was also tested. Prior to infusion, the mean blood CD4+CD25+ cells/mm3 was 126, which was 26.8% of CD4+ T cells. This decreased to a mean of 78 cells/mm3 blood and mean of 19.0% of CD4+ T cells 3-5 days after Ontak. Also, interferon-γ-expressing T cells increased approximately 50% and FOXP3 (a functional marker for Tregs) was reduced after Ontak. In patient 4, CD4+CD25+ cells inhibited T cell proliferation in vitro prior to but not after treatment. Further, a single Ontak-mediated Treg depletion reduced blood CA-125 from 121 to 38 U/mL four weeks later in patient 4, suggesting clinical efficacy. Patient 4 then received 6 additional doses of Ontak at 12 μg/kg with a further decrease in blood CA-125 level to 16 U/mL four weeks after the final dose. Additionally, a PET/CT fusion demonstrated dramatic reduction of metastatic disease. The CA-125 level remains normal two months after the final Ontak dose. Our data demonstrate for the first time that Ontak efficiently depletes Tregs in patients with cancer, and Treg depletion is associated with improved T cell immunity, normalized CA-125 and reduced tumor metastasis. The data may help explain failures of current tumor immunotherapy protocols. It further suggests that Treg depletion or a combination with current immunotherapeutic regimens will be a novel strategy for treating patients with cancer.